Analysis and verification of harmonic interaction between DDWTs based on αβ stationary coordinate system. Issue 10 (25th March 2020) - Han, Pingping; Wang, Longjian; Dou, Sheng; Wang, Lei; Bi, Rui; Yang, Xiangzhen
Abstract : This study presents an analysis method of harmonic interaction characteristics between direct‐drive wind turbines (DDWTs) based on αβ coordinates and the relative gain array (RGA). First, considering the digital delay of inverters, the capacitive current feedback active damping is applied to suppress the resonance of LCL filter, and the output current of DDWT is regulated by quasi‐proportional resonant controller in the αβ coordinates and then combined with the topology of the direct‐drive wind farm (DDWF), the transfer function matrix of the DDWF is established. Second, based on the RGA principle, the relationship between parameters and harmonic interaction characteristics is quantitatively analysed. The results show that with the proportional coefficient increasing, the degree of negative interaction between DDWTs is strengthened, which increases the harmonic content in the negative interaction frequency band. However, the increase of resonance coefficient and number of DDWTs will weaken the degree of negative interaction. In addition, with the increase of capacitive current feedback coefficient and grid inductance, the interaction frequency gradually decreases. Finally, the DDWF model is built both on Matlab/Simulink and StarSim + PXI hardware‐in‐the‐loop platform to verify the analytical results. The harmonic interaction characteristics can be used to guide the parameter design of DDWTs, so as to optimise power quality of the wind farm.